THE EFFECTIVENESS OF THE WHATSAPP GROUP APPLICATION USE PROGRAM FOR EDUCATORS DURING THE COVID-19 PANDEMIC - Nur Holifah; Lutfia Nurul Hidayati (Program Studi Doktor Ilmu Administrasi, FISIP, Universitas 17 Agustus 1945 Surabaya, 2021)
This research was conducted based on the background of problems in the Education sector during the Covid-19 pandemic. Where the implementation of face-to-face learning is limited, it is a condition where students and teachers cannot meet in-person to maintain social distancing and physical distancing during this pandemic which makes learning to be done through online learning. Where so far teaching and learning activities are carried out conventionally, namely face to face. In online learning, we recognize the terms synchronous and asynchronous learning. The use of various applications during online learning is considered more effective and efficient because it makes it easier for users to access all kinds of information and to stop the spread of the virus. This study seeks to see how the effectiveness of the WhatsApp group (WAG) application program on the performance of educators at Wachid Hasyim I High School Surabaya during the Covid-19 pandemic. The theory used is the theory of program effectiveness and the theory of performance. This type of research is descriptive qualitative using data collection techniques, namely interviews, observations, documentation, and questionnaires. The data analysis used is the collection, reduction, display, and verification. The results of this study are first, the program using the WhatsApp group application at SMA Wachid Hasyim 1 Surabaya as the main media in online learning activities is said to be effective and efficient because the WhatsApp group application is very quota-efficient, easily accessible anywhere, and helps facilitate the delivery of information so that it can be accessed easily. coordination related to teaching and learning activities is carried out. Second, regarding the effectiveness of the program using the WhatsApp group application on the performance of educators at SMA Wachid Hasyim I Surabaya during the pandemic, it is said to have not been effective. Because the use of the WhatsApp group application as the main media for online learning activities is not optimal in delivering material and greatly affects the performance of educators.